Physical Approaches to Prevent and Treat Bacterial Biofilm - Alexa A. Ciarolla; Norman Lapin; Dustin Williams; Rajiv Chopra; David E. Greenberg (Antibiotics, 2022)
Prosthetic joint infection (PJI) presents several clinical challenges. This is in large part due to the formation of biofilm which can make infection eradication exceedingly difficult. Following an extensive literature search, this review surveys a variety of non-pharmacological methods of preventing and/or treating biofilm within the body and how they could be utilized in the treatment of PJI. Special attention has been paid to physical strategies such as heat, light, sound, and electromagnetic energy, and their uses in biofilm treatment. Though these methods are still under study, they offer a potential means to reduce the morbidity and financial burden related to multiple stage revisions and prolonged systemic antibiotic courses that make up the current gold standard in PJI treatment. Given that these options are still in the early stages of development and offer their own strengths and weaknesses, this review offers an assessment of each method, the progress made on each, and allows for comparison of methods with discussion of future challenges to their implementation in a clinical setting.